A comparison of efficacy of endovascular versus surgical repair for the treatment of arteriovenous fistula stenosis in Taiwan. Issue 3 (May 2017) - Fan, Szu-Shan; Chen, Chien-Wen; Lu, Kuo-Cheng; Mao, Hung-Chung; Chen, Miao-Pei; Chou, Chu-Lin
Background: Percutaneous transluminal angioplasty (PTA) and fistula reconstruction surgery are therapeutic options for vascular access occlusion in hemodialysis patients. However, owing to its convenience, PTA has gradually become the preferred therapeutic option for fistula stenosis or occlusion. This study investigated the effects of the two therapeutic methods on the vascular access maintenance duration (number of days) and maintenance costs of fistula in dialysis patients from different dialysis units. Methodology: In this study, 544 hemodialysis patients from 2 dialysis units in a teaching hospital in the southern area of Taiwan were included in the analysis of the frequency of PTA or revascularization surgery and the use of related medical resources by conducting a retrospective chart review. Results: The frequency of PTA in the patients undergoing long-term hemodialysis was not significantly associated with their demographic characteristics. The efficacy of PTA has declined with shorter maintenance duration with increasing PTA frequency. The cost profile of PTA was more expensive than that of fistula revascularization surgery. Conclusions: In this study, PTA was found to be just a temporary solution for fistula thrombosis, whereas fistula reconstruction surgery is inexpensive and improves survival time. Therefore, dialysis units should establish an appropriate standard of care to avoid over-reliance on PTA in order to reduce the fistula failure rate, improve the dialysis efficacy, and reduce the psychological stress in patients, as well as to reduce the maintenance costs and rationalize the medical expenses.